Analysis of Basic Environmental Health Facilities Associated with Risk Factors of Diarrhea Among Toddlers - Maliga, Iga; Rafi'ah, Rafi'ah; Lestari, Ana; Hasifah, Herni; Sholihah, Nur Arifatus (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Diarrheal disease in young children (toddlers) seems increasingly common in tropical countries, especially in dirty and dense urban areas. Diarrhea can last several days and cause the body to lose the fluids needed for survival. This study aimed to determine the sanitation factors that influence the incidence of diarrhea. Methods: This study used a case-control design involving 100 respondents. All respondents were divided into two groups: the case class (toddlers who had diarrhea) and the control class (toddlers who did not experience diarrhea). Results and Discussion: This showed that four sub-variables of sanitation (waste, drainage conditions, domestic wastewater management, and water source safety) had a significant relationship with the incidence of diarrhea (p-value 0.05). Domestic wastewater was the most influencing factor and securing clean water and drinking water sources, with a Nagelkerke R Square value of 0.952. There was an indication that the independent variable (sanitation) affected the dependent variable (diarrhea incidence) by 95.2%. Conclusion: The sub-variable of domestic wastewater management and the sub-variable of the safety of clean water and drinking water sources were the most affecting the incidence of diarrhea. The clean water source factor was 12 times riskier. It means children who did not get it will have 12 times the risk of getting diarrhea. Meanwhile, in the aspect of domestic wastewater management, children who did not meet the requirements for domestic wastewater have a risk of 8.13 times the incidence of diarrhea.